La tutela laboral de los derechos fundamentales del trabajador. Una asignatura pendiente en tiempos de reforma - Arce Ortiz, Elmer Guillermo (2012)
The labor guardianship of worker’s fundamental rights: A pending subject in times of reform The articlestarts with the penetration of Constitutional Law in labor relations mainly promoted by the Constitutional Court, which with its repeated statements have specified the normative content of workers’ constitutional rights. From this, it maintains that in protection matters of fundamental rights we are in the middle of an insufficientordinary route and another extraordinary route, legal protection, also unable to assume adequate protection of workers. The article analyzes particularities that should have a claim of violation of the fundamental rights of any other in alabor site to pick up characteristics such as:  accentuated swiftness, priority and preventing inadmissibility “in limine”. Finally, the text concludes regretting that New Procedural Labor Lawhasn’t created an ad hoc process for the protection of fundamental rights and that, on the contrary, it has opted for a disperse and chaotic system to protect them.